Molecular Interaction and Crystalline Structure Reorganization of C. esculenta and M. leucadendra Extract-Loaded CS/PVA Electrospun Nanofibers - Atina Atina; Idha Royani; Assa Idah; Miksusanti Miksusanti; Fitri Suryani Arsyad (Science and Technology Indonesia, 2026)
Understanding the molecular-to-structural evolution of extract-loaded electrospun systems is essential for rationally designing biofunctional nanomaterials. In this study, chitosan/polyvinyl alcohol (CS/PVA) electrospun nanofibers incorporated with Colocasia esculenta (CE) and Melaleuca leucadendra (ML) extracts were systematically investigated to elucidate the correlation between precursor solution interactions and resulting fiber morphology. Raman and UV-Visible spectroscopy were employed to probe molecular interactions and electronic transitions in electrospinning solutions. Extract incorporation induced vibrational band broadening and intensity suppression in Raman spectra, accompanied by increased absorbance and a red shift in UV–Visible spectra, particularly in the ML-containing system, indicating enhanced hydrogen bonding and greater electronic delocalization. Following electrospinning, structural characterization using XRD, FTIR, and SEM revealed progressive crystallinity reduction, peak shifting toward lower diffraction angles, hydrogen-bond-driven band broadening, and morphological evolution from smooth 90.86 ± 1.87 nm fibers (CS/PVA) to thicker 111.89 ± 2.96 nm fibers (CS/PVA/CE) and 118.48 ± 2.98 nm fibers (CS/PVA/ML). No separate crystalline extract phase was detected, confirming molecular-level dispersion within the polymer matrix. The ML-modified system exhibited the highest degree of amorphization and structural reorganization. These results establish a direct structure–property–function relationship, demonstrating that extract-induced modulation of intermolecular interactions governs crystalline organization, electrospinning dynamics, and nanofiber morphology. This study provides mechanistic insight into crystallinity engineering in plant-extract-loaded polymer systems and offers a scalable strategy for designing advanced bioactive electrospun nanomaterials.